Is reduction better than arthrodesis in situ in surgical management of low-grade spondylolisthesis? A system review and meta analysis - Bai, Xuedong; Chen, Jiahai; Liu, Liyang; Li, Xiaochuan; Wu, Yaohong; Wang, Deli; Ruan, Dike (European spine journal, 2017)
Purpose To compare the clinical and radiographic outcomes of arthrodesis in situ with arthrodesis after reduction in low-grade spondylolisthesis. Methods We performed a comprehensive search of both observational and randomized clinical trials published up to April 2016 in PubMed, MEDLINE, Cochrane Library, and Embase databases. The outcomes included age, sex, operative time, blood loss, and at least 2 years clinical results of Oswestry disability index (ODI), visual analogue scale (VAS), lumbar lordosis, slippage, fusion rate, the rate of good and excellent and the complication rate. Two authors independently extracted the articles and the predefined data. Results Seven eligible studies, involving four RCTs and three cohort studies were included in this systematic review and meta-analysis. Patients who underwent reduction did achieved better slippage correction comparing with arthrodesis in situ ( P < 0.00001). However, there was no significant difference in the case of operative time, blood loss, VAS ( P = 0.36), ODI ( P = 0.50), lumbar lordosis ( P = 0.47), the rate of good and excellent ( P = 0.84), fusion rate ( P = 0.083) and complication rate ( P = 0.33) between the arthrodesis in situ group and the reduction group. Conclusions On the basis on this review, arthrodesis after reduction of low-grade spondylolisthesis potentially reduced vertebral slippage. Reduction was neither associated with a longer operative time nor more blood loss. There was no significant difference in the outcomes between reduction and arthrodesis in situ group. Both procedures could be expected to achieve good clinical result. Level of evidence Therapeutic Level IIa.